Assessments of pain, functional impairment, anxiety, and depression in US adults with hemophilia across patient‐reported outcome instruments in the Pain, Functional Impairment, and Quality of Life (P‐FiQ) study. (2nd March 2018) - Buckner, Tyler W.; Batt, Katharine; Quon, Doris; Witkop, Michelle; Recht, Michael; Kessler, Craig; Baumann, Kimberly; Hernandez, Grace; Wang, Michael; Cooper, David L.; Kempton, Christine L.
Abstract: Introduction: Pain, functional impairment, anxiety, and depression associated with joint disease may affect health‐related quality of life (HRQoL) in people with hemophilia. Objective: To report detailed patient‐reported outcomes (PRO) assessments related to HRQoL in participants in the Pain, Functional Impairment, and Quality of Life (P‐FiQ) study. Methods: Pain and HRQoL were assessed via PRO instruments in US adult males with hemophilia A or B and a history of joint pain or bleeding. PRO instruments included EQ‐5D‐5L with visual analog scale, Brief Pain Inventory v2 Short Form, SF‐36v2, and Hemophilia Activities List. Instrument domain and item responses were described. Results: Responses were collected from 381 adult males with a median age of 34 years. Pain was observed across instruments and affected daily activities and quality of life. Respondents reported functional impairment that limited the kind of work and activities they participated in, with activities involving the lower extremities being most affected. A high prevalence of mental health disorders was identified across instruments. Conclusions: Pain and HRQoL were evaluated using multiple PRO instruments, which vary in timescales of assessment and levels of detail. More consistent clinical assessments and patient dialog regarding pain and aspects of HRQoL may help drive improved outcomes.